2021
DOI: 10.3928/1081597x-20210105-03
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Tomographic Analysis Among Patients With Thyroid Gland Dysfunction

Abstract: PURPOSE: To analyze the corneal tomographic parameters of patients with thyroid gland dysfunction. METHODS: This case–control study included 100 eyes of 50 patients with thyroid gland dysfunction and 100 eyes of 50 healthy controls. All eyes were examined by Pentacam (Oculus Optikgeräte GmbH). Pentacam parameters were compared between patients with thyroid gland dysfunction and controls. Spearman's correlation coefficient between different Pentacam para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…This agreed with Carreira et al, who assessed the tear film stability and corneal epithelial thickness in patients with GD with and without Graves orbitopathy and showed that the level of eye dryness and corneal thinning were higher in GD regardless of GO status [25]. A study by Bassioujny et al, who used the Pentacam (Oculus Optikgeräte GmbH) to evaluate the cornea of patients with thyroid gland dysfunction and controls and revealed that patients with hyperthyroidism tend to have thinner corneas and more abnormal tomographic parameters correlating with keratoconus [26]. Alternative research on tear film evaluation used other methods in TED, such as Alanazi et al, who employed the phenol red thread test followed by the TBUT test with a 10-min break between the tests.…”
Section: Discussionmentioning
confidence: 99%
“…This agreed with Carreira et al, who assessed the tear film stability and corneal epithelial thickness in patients with GD with and without Graves orbitopathy and showed that the level of eye dryness and corneal thinning were higher in GD regardless of GO status [25]. A study by Bassioujny et al, who used the Pentacam (Oculus Optikgeräte GmbH) to evaluate the cornea of patients with thyroid gland dysfunction and controls and revealed that patients with hyperthyroidism tend to have thinner corneas and more abnormal tomographic parameters correlating with keratoconus [26]. Alternative research on tear film evaluation used other methods in TED, such as Alanazi et al, who employed the phenol red thread test followed by the TBUT test with a 10-min break between the tests.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies mostly analysed corneal thickness in patients with TED [ 15 , 16 ] and hypothyroidism [ 7 , 17 , 18 , 19 , 20 , 21 ]. In a study that included 27 individuals with TED and 30 healthy individuals, Karabulut et al did not observe a significant difference in central corneal thickness between patients with TED and healthy individuals (with Goldmann-correlated intraocular pressure (IOPg) and corneal-compensated IOP (IOPcc) being significantly increased and corneal hysteresis (CH) being significantly decreased in patients with TED) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study that included 48 patients with HT and 49 healthy controls did not observe a significant difference in central corneal thickness between these two groups, while IOPcc was significantly higher in the HT group [ 17 ]. However, Bassiouny et al concluded that thyroid gland dysfunction contributes to the development of corneal tomographic changes [ 21 ]. In a study that included 50 patients with thyroid gland dysfunction and 50 healthy individuals, the authors observed a significant increase in central corneal thickness levels in patients with hypothyroidism in comparison to both healthy individuals and patients with hyperthyroidism [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of thyroid gland dysfunction was reported in KC patients. Thyroxin was found to cause biochemical changes in the corneal stroma as a result of thyroxin-receptor interaction [8][9][10][11]. Vitamin D receptors (VDR) are found in the cornea, lens, and retinal pigment epithelium [12,13].…”
Section: Introductionmentioning
confidence: 99%